Child and adult mortality in Zimbabwe, 1980-2005 - Marera, Double-Hugh (Centre for Actuarial Research (CARE), 2014)
This research applies direct and indirect methods to data from censuses and Demographic and Health Surveys to derive empirical estimates of the level and trends of child and adult mortality in Zimbabwe from 1980 to 2005.